An Analysis of Figurative Language in â€œBorn For Thisâ€, â€œThatâ€™s What You Getâ€ and â€œThe Only Exceptionâ€ Songs by Paramore - Anjar Dwi Cahyo; Masulah -; Ari Setyorini (Tell : Teaching of English Language and Literature Journal, 2014)
The analysis provides the study about figurative language, possible meaning and the total meaning in three songs of Paramore, â€œBorn for Thisâ€, â€œThatâ€™s What You Getâ€ and â€œThe Only Exceptionâ€. This study tries to analyze figurative language, possible meaning and the total meaning in statement of the problem. This analysis aims to analyze the types of figurative language and possible meaning and to tell the total meaning of the Paramore songs. This analysis follows the design of qualitative method because it is related to the object of research. Qualitative description is defines as research designed to produce a low inference description of a phenomenon that draws from discourse.The result of the research of the first song is â€œBorn for Thisâ€. This song has figurative language are ambiguity, personification, and etc. â€œThatâ€™s What You Getâ€song has ambiguity, personification, and etc. â€œThe Only Exceptionâ€ has personification, metaphor and etc. From this research the researcher concludes, in this songs have many figurative languages to make meaningful.